Rarity Status and Habitat of Shorea laevis and Shorea leprosula in Muara Teweh, Central Kalimantan - Sri Wilarso Budi; Iskandar Zulkarnaen Siregar; Ulfah Juniarti Siregar; Andi Sukendro; Prijanto Pamoengkas; Tedi Yunanto (Institut Pertanian Bogor (IPB University), 2012)
Forest exploitation and conversion to other landuse may cause lost of biodiversity, including most important dipterocarp trees species, i.e. Shorea leprosula and Shorea laevis. The objective of this study was to determine the rarity status of the two important shorea species, i.e. S. laevis and S. leprosula, based on IUCN criteria, their habitat characteristics, and their association with other species, as one of the basis for determining their conservation strategy as a part of forest management. This study was conducted in three types of ecosystem (virgin forest, secondary forest, and fragmented forest) in Muara Teweh, Central Kalimantan. Methodology used in this research includes vegetation and tree diversity analysis. Study results showed that both S. laevis and S. leprosula were included within category of “low risk” in the 3 types of ecosystem in the forest area being studied. Habitat characteristics which determined the absence of S. laevis in the virgin forest habitat was the soil permeability which was too low, whereas other soil chemical and physical properties in the three types of ecosystems were relatively similar. Presence of S. laevis were positively associated with species of S. uliginosa, Dialium platysepalum, Dipterocarpus ibmalatus, Palaquium rostatum, Vatica rasak, Adinandra sp., and Memecyclon steenis. On the other hand, S. leprosula were positively correlated with S. kunstleri, Castanopsis sp., Shorea sp., Quercus bennettii, Castanopsis argentea, and D. hasseltii.